Case study of prototype and small-scale model behavior of clay blocks masonry under compression. (December 2021) - Milani, Alisson Simonetti; Lübeck, André; Mohamad, Gihad; Santos Neto, Almir Barros da Silva; Budny, Jaelson; Kosteski, Luis Eduardo
Abstract: The small-scale models have been used for decades to reproduce the strength and failure behaviour in Engineering problems. The main goal of this study was to analyse the scale factor between masonry components prototypes and models to preview the mechanical properties of hollow clay blocks masonry under compression. For this purpose, it was tested full and small-scale of hollow clay blocks, wallettes and two-blocks-high stackbond prisms with a reduction proportion of 1:5. The sand of the bedding mortar on small-scale model was graduated according to the sand maximum diameter. Compressive, splitting tensile strength and elastic modulus of the blocks, prisms and wallettes were determined during experimental tests. It was also determined the vertical and horizontal strain of masonry wallettes. From experimental results it was possible to conclude that the strength ratio between full and small-scale models were 1.27, 2.05 and 2.75 for blocks, prisms and wallettes, respectively. When it was compared the elastic modulus ratio between full and small-scale, the results were 1.16, 1.32 and 1.28 for blocks, prisms and wallettes, respectively. The failure mode of masonry specimens was too similar between full and small-scales, indicating that for blocks, prisms and wallettes components could be used to represent strength and strain behavior of masonry under compression.